Description of two smallest field crickets from South America, Laureopsis nauta Jaiswara gen. nov., sp. nov. and Perugryllus estiron Jaiswara gen. nov., sp. nov. (Orthoptera, Grylloidea, Gryllidae, Gryllinae) - Jaiswara, Ranjana; Desutter-Grandcolas, Laure (Zootaxa, 2017)
Gryllinae are one of the most diverse and widely distributed cricket groups. However, in South America they are known only from 10 genera. We update this list by describing two new genera and species of field crickets i.e. Laureopsis nauta Jaiswara gen. nov., sp. nov. and Perugryllus estiron Jaiswara gen. nov., sp. nov. from Peru.